Rtd-a controller : an alternative to pid control? - Ng, Zhen Fu. (2010)
(R)obustness, setpoint (T)racking, (D)isturbance rejection and overall (A)ggressiveness(RTD-A) controller has been proposed for control of single input single output (SISO)systems as an alternative to the Proportional-Integral-Derivative (PID) controller. In this project, the RTD-A algorithm is analyzed and a block diagram representation is proposed. The block diagram representation resembles an internal model control (IMC)structure. The controller comprises of a set-point tracking filter, a generalized analytical predictor (GAP), a robustness filter and a controller designed according to IMC structure.It is found that the claim of transparent tuning for RTD-A controller only holds true if there is no plant-model mismatch. Subsequently, a set of tuning strategy has also been proposed based on the knowledge of the various blocks and controller parameters. The RTD-A controller has also been extended to integrating and underdamped systems and the controller was able to achieve zero offset for both set point tracking and load disturbance rejection.